(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the post operative hospital stay and in-hospital complications of total hip replacement (THR) in Lady Reading Hospital Peshawar. Methods: This Descriptive study was conducted in Department of Orthopedic and Trauma, Medical Teaching Institute Lady Reading Hospital Peshawar from 21st February 2020 to 21st October 2021. All patients with Osteoarthritis hip fulfilling the inclusion criteria and operated with cemented total hip arthroplasty were included in this study. Risk Assessment and Prediction Tool (RAPT) Score was calculated pre-operatively for every patient and hospital stay was arranged accordingly and documented any in hospital complications. Patients with RAPT score of less than 6 were labelled as high risk,6 to 9 score medium risk and more than 9 score were labelled as low risk for in-hospital rehabilitation. Results: In this study 39 patients were included. Male patients were 26(66.7%) and female were 13(33.3%). The mean age was 63.05± 4.359 years. Left sided hip was operated in 17 (43.6%) patients and right side in 22(56.4%) patients. Pre-operative Risk Assessment and Prediction Tool (RAPT) Score was less than 6 in 3(7.7%) patients, 6 to 9 in 16(41.0%) and more than 9 in 20(51.3%) patients. The mean post operative hospital stay was 4.28±1.65 days(range 2 to 7 days).The mean post operative hospital stay of three days was noted in 11(28.2%) patients, five days in 8(20.5%) and six days in 7(17.9%). There were 2(5.12%) cases of superficial surgical site infection. Conclusion: The mean post operative hospital stay was short and in-hospital complications were minimum in our series. Preoperative assessment with Risk Assessment and Prediction Tool (RAPT) Score predicted hospital stay accurately in majority of our patients,